2020
DOI: 10.3892/etm.2020.8569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mevalonate kinase interference on cell differentiation, apoptosis, prenylation and geranylgeranylation of human keratinocytes are attenuated by farnesyl pyrophosphate or geranylgeranyl pyrophosphate

Abstract: Mevalonate kinase (MVK) mutations were previously identified in disseminated superficial actinic porokeratosis. However, the role of MVK in differentiation, apoptosis and prenylation of keratinocytes requires further investigation. Farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP) of the mevalonate pathway attach to small G proteins, and serve as molecular switches in biochemical pathways. Therefore, the aim of the present study was to investigate the role of MVK in the expression of keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…MVK shRNA experiments in a keratinocyte cell line decreased expression of differentiation markers, protein prenylation and increased apoptosis. These effects were reversed upon addition of FPP or GGPP to the cells (122).…”
Section: Other Disease Phenotypes Related To Mkdmentioning
confidence: 95%
“…MVK shRNA experiments in a keratinocyte cell line decreased expression of differentiation markers, protein prenylation and increased apoptosis. These effects were reversed upon addition of FPP or GGPP to the cells (122).…”
Section: Other Disease Phenotypes Related To Mkdmentioning
confidence: 95%
“…This process interferes with the function of Ras and Rho family GTPases [153][154][155][156][157]. Indeed, lower GGPP and FPP concentrations, leading to reduced RAS and Rho isoprenylation, signal transduction, and DNA synthesis, are important functional consequences of statins in the treatment of cancer [119,[158][159][160][161][162]. Inhibiting the farnesylation of these proteins restricts their activity and might hinder cancer cell proliferation [163,164].…”
Section: Non-cholesterol-mediated Pathwaysmentioning
confidence: 99%
“…These mutations result in the persistent activation of Ras, which, accordingly, leads to the uncontrolled proliferation of cells. It was revealed that the inhibition of farnesylation of mutated Ras inhibits its activity in cancer cells, indicating that the inhibition of farnesylation seems to offer a vital means of hampering cancer progression [ 124 , 125 ]. On the contrary, interfering with RhoA-mediated signaling pathways by preventing geranylgeranylation might affect other cellular processes that are important for cancer progression, such as migration, invasion, and apoptosis [ 126 , 127 ].…”
Section: Anticancer Effects Of Statinsmentioning
confidence: 99%